МЕТОД ШИРОТНО-ІМПУЛЬСНОГО РЕГУЛЮВАННЯ ПОТУЖНОСТІ РОЗРЯДНИХ ДЖЕРЕЛ СВІТЛА - Лупенко, А.; Мовчан, Л.; Натяга, В.; Сисак, І. (Інститут електродинаміки НАН України, Київ, 2011)
An output stage of high-frequency electric motor-starting device (EMSD) with time-proportional control of discharge lamps performed after the diagram of resonance half-bridge inverter with asymmetric control has been analyzed. In series oscillatory circuit a lamp is connected parallel to capacitor. Dependences of instantaneous current of lamp inductance and voltage on duty cycle of inverter pulses in steady-state have been established. Controlled characteristics of EMSD under different values of characteristic impedances were calculated. Material effect of loop characteristic impedance on duty cycle range is shown. In this article it has been mentioned that when designing initial stage of EMSD the characteristic impedance should be coordinated with the stage supply voltage secured the duty cycle approximate to 0,5 at lamp rating. To verify the proposed approach an experimental characteristic "duty cycle – power" for the lamp DF-40 was taken. Calculation results conform well to experimental results. References 7, figures 5.